THE EFFECT OF AUDIT QUALITY, ACCOUNTABILITY AND INTERNAL CONTROL ON THE QUALITY OF FINANCIAL REPORTS IN ZAKAT MANAGEMENT - Anisya Anggreini; Adam Zakaria; Indra Pahala (Transpublika Publisher, 2023)
The quality of financial reports is a structured report regarding the statement of financial position and transactions carried out and accounted for by a reporting entity. The quality of financial reports is considered good if the information presented in these reports can be understood and meets the needs of users in making decisions. It should be free from misleading notions, material errors, and should be reliable, allowing for comparisons with previous periods of financial statements. This research was conducted to determine the effects of audit quality, accountability, and internal control on the quality of financial reports. The research focused on the Amil Zakat Institute and the National Amil Zakat Agency for the City of Depok and DKI Jakarta as the population. The research sample was selected using purposive sampling methods and included 30 respondents. Data were processed using SPSS software and analyzed using multiple linear regression analysis. The results of this study indicate that audit quality, accountability, and internal control have a positive effect on the quality of financial reports.